2008
DOI: 10.1002/ca.20633
|View full text |Cite
|
Sign up to set email alerts
|

Histo‐Topographic study of the longitudinal anal muscle

Abstract: The longitudinal anal muscle (LAM) has been described as a vertical layer of muscular tissue interposed between the circular layers of the internal (IAS) and external (EAS) anal sphincters. There is, however, no general agreement in the literature on its composition and attachments. The aim of this study was to investigate the histological structure, attachments, and topography of the LAM in order to evaluate its role in continence and defecation, thus enhancing knowledge of the surgical anatomy of this region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 23 publications
1
41
1
Order By: Relevance
“…We were unable to find the pubo-analis, i.e., the innermost part of the puborectalis (Macchi et al 2008;Fröber et al 2001), even though an intergender difference has been reported. The present fetuses did not show a tight connection between the internal anal sphincter and conjoining longitudinal coat, in contrast to the adult morphology described by Arakawa et al (2004).…”
Section: Perineal Body and Other Structuresmentioning
confidence: 58%
“…We were unable to find the pubo-analis, i.e., the innermost part of the puborectalis (Macchi et al 2008;Fröber et al 2001), even though an intergender difference has been reported. The present fetuses did not show a tight connection between the internal anal sphincter and conjoining longitudinal coat, in contrast to the adult morphology described by Arakawa et al (2004).…”
Section: Perineal Body and Other Structuresmentioning
confidence: 58%
“…As well as the vascular wall, in the pelvic floor, smooth muscle and elastic fibers coexist (Figures 1(e), 2(b), 3(b), and 3(e)). For the anorectum, the LA insertion provides a smooth muscle-rich connective tissue band that is continuous with the conjoint longitudinal muscle coat [20] (Figures 4(c) and 4(d)) or longitudinal anal muscle [37]. The interface smooth muscles are also continuous with the rectourethralis muscle [38] (Figure 5(b)).…”
Section: Methodsmentioning
confidence: 99%
“…2,3,12 However, histologic studies suggest that the LRM muscle cannot be such a thick structure because it comprises so few smooth muscle fibers. 13 The results of 3-dimensional positioning in the current study indicate that this thick muscular layer is indeed the vertical levator (Fig. 2B) and that the vertical levator was mistaken for the LRM muscle in the study by Rociu et al 2,3,12 New MRI signs in the current study show that the caudal end of the vertical levator becomes a series of tendinous-like cords below the plane of the deep sphincter (Fig.…”
Section: Discussionmentioning
confidence: 73%